The Effectiveness Of The Three-Step Interview Technique In Improving Students’ Speaking Ability At SMK Negeri 3 Padangsidimpuan - Sikumbang, Abdul Azis; Sari, Siti Meutia; Meidipa, Lisa Fitri (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
This study aimed to determine the effectiveness of the Three-Step Interview Technique in improving the speaking ability and classroom participation of eleventh-grade students at SMK Negeri 3 Padangsidimpuan. Employing a Classroom Action Research (CAR) design, the study was conducted in two cycles involving 72 students selected by cluster random sampling. Data were collected through pre-tests, post-tests, and student observation sheets. The results showed that the students' speaking ability significantly improved, with mean scores increasing from 57.08 in the pre-test to 81.46 in the post-test Cycle II, representing a 42.70% improvement. Additionally, student participation scores remained consistently high, indicating strong engagement throughout the intervention. The findings suggest that the Three-Step Interview Technique is an effective cooperative learning strategy to enhance students' speaking competence and classroom interaction. The study recommends the wider application of this technique in EFL classrooms to foster communicative competence in a supportive learning environment.